English Self-Regulated Language Learning on Youtube: Students’ Purpose, Perception and Action - Retnaningsih, Woro; Milaningrum, Elisabeth; Nugroho, Arif; Putra, Heldy Ramadhan (Jurnal Pendidikan Progresif, 2022)
English Self-regulated Language Learning on Youtube: Students’ Purpose, Perception, and Action. Objective: This study scrutinizes English learners’ self-regulated language learning using Youtube beyond the formal classroom. Methods: to reach the objective, a qualitative inquiry approach was employed in this study. Twenty-two university students in Central Java province Indonesia who had substantial experiences of watching English-teaching videos were purposively invited for a semi-structured interview to depict how they performed self-directed learning. The data were qualitatively analyzed by classifying based on the main themes, coding, reviewing, and conclusion drawing Findings: the results portrayed that the most dominant goals of self-directed language learning on Youtube were to look for more learning sources, to enhance English skills and vocabulary, and to explore cultural knowledge. Another finding showed that learning English on Youtube was more interesting and flexible without time and space restriction. Conclusion: Youtube videos offers a fertile ground for educational purposes, particularly for developing English skills in a self-directed learning beyond formal classroom. Keywords: english-teaching on youtube; self-regulated language learning; informal learning.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202218